The Model of Character Education Reinforcement of Bandung Masagi From A Sound Governance Perspective - Nur, Mohamad Ichsana; Fathujaman, Fathujaman (Department of Public Administration, 2023)
The number of crime cases in the city of Bandung such as persecution, narcotics, theft, bullying and hoax have been increasing on social media. The Impact of new era development which is continuously rising, including the influence of cyberspace which is very dominating, looks paradoxical with the mentality of the citizens who fell down. One of the causes is the multidimensional crisis which leads to the fading of national morality. This is the background of the Bandung City government issued Perwal No. 420 of 2016 concerning Bandung Masagi Character Education. The objectives to be achieved in this research are to analyze the implementation Bandung Masagi program in Sound Governance Perspective. This research uses the qualitative approach along with the descriptive method. The data were collected by in-depth interviews and study of literature. The results of this research reveal that